Latent heat storage microcapsule and its manufacturing method

By using latent heat storage microcapsules of gallium or gallium alloy cores and gallium oxide or gallium hydrate shells in electric vehicles, the existing PCM problems of low thermal conductivity and limited space are solved, and the effects of high thermal conductivity, thermal storage density and soft shape are achieved.

CN114341309BActive Publication Date: 2025-03-14HOKKAIDO UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080060730.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-27
Filing Date
2020-08-27
Publication Date
2025-03-14
Estimated Expiration
2040-08-27

AI Technical Summary

Technical Problem

The existing PCM has low thermal conductivity and cannot absorb heat quickly. At the same time, the space for heat storage materials for electric vehicles is limited, so it is necessary to develop latent heat storage bodies that can softly change shape.

Method used

The latent heat storage microcapsules containing a core of gallium or gallium alloy and with gallium oxide or gallium hydrate as the shell are manufactured through particle shaping process, water treatment process and oxidation treatment process.

Benefits of technology

The thermal conductivity and thermal storage density of the latent heat storage microcapsules are improved, making their shape soft, suitable for configuration in a limited space, and have high thermal durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114341309B_ABST
    Figure CN114341309B_ABST
Patent Text Reader

Abstract

The latent heat storage microcapsule comprises: a core comprising gallium or a gallium alloy, and a shell covering the core and comprising gallium oxide or gallium hydrate. The manufacturing method thereof comprises: a particle forming step of forming liquid gallium or gallium alloy into particles, a water treatment step of heating the particles in distilled water to form gallium hydrate on the surface of the particles, and an oxidation treatment step of oxidizing the gallium hydrate to form a shell comprising gallium oxide. In addition, the manufacturing method thereof comprises: a particle forming step of forming liquid gallium or gallium alloy into particles, a cooling step of cooling the particles into a solid state, and a pH treatment step of immersing the particles in an aqueous solution of a predetermined pH to form a shell comprising gallium hydrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a latent heat storage microcapsule and a method for producing the same, and in particular to a latent heat storage microcapsule in which a core containing gallium or a gallium alloy is covered with a shell containing gallium oxide or gallium hydroxide and a method for producing the same. Background Art

[0002] In recent years, the development of lithium-ion batteries has been continuously promoted, and the high output and high capacity of batteries have developed rapidly. However, in order to optimize battery characteristics, prolong life, and further improve safety, a high level of thermal management of batteries is required. For example, when the battery is charged and discharged, there is a concern that the cell temperature rises due to the heat generated by the battery cell, resulting in deterioration of battery performance and thermal runaway. Therefore, it is necessary to maintain the cell temperature at the optimal temperature (about ~50°C) during the battery charging and discharging.

[0003] In addition, although the cruising range of electric vehicles has been improved, on the other hand, the reduction in cruising range caused by the power consumption for cooling in summer and heating in winter is becoming a problem. If the heat generated in the car can be absorbed by a heat pump and effectively used for cooling or heating, the reduction in cruising range can be prevented. However, unlike internal combustion engine vehicles with large heat sources such as engines, electric vehicles have a small heat generation process and heat generation amount, so a high-level thermal management technology is required to more effectively collect heat.

[0004] In view of this, PCM (Phase Change Material) may be used as a heat buffer to absorb the heat generated by lithium-ion batteries and maintain the temperature inside the module at a certain level. In addition, by arranging PCM at each heat generating site and recovering the heat generated intermittently at multiple sites, it may also be used as a heat source at a certain temperature. Therefore, the use of a latent heat storage body obtained by wrapping an organic compound such as normal alkane with a seamless metal bag has been proposed (for example, refer to Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-215745 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, PCM generally has low thermal conductivity. For example, the thermal conductivity of the latent heat storage body is very low, about 0.21 W / m·K, and there is a problem that heat cannot be absorbed quickly. In addition, the space for heat storage materials inside electric vehicles is extremely limited, so it is necessary to develop a latent heat storage body that can flexibly change shape.

[0010] Therefore, an object of the present invention is to provide a latent heat storage microcapsule having a higher thermal conductivity than conventional PCM and capable of flexibly changing its shape, and a method for producing the same.

[0011] Means for solving problems

[0012] One embodiment of the present invention is a latent heat storage microcapsule comprising:

[0013] A core comprising gallium or a gallium alloy, and

[0014] A shell covers the core and comprises gallium oxide.

[0015] Another aspect of the present invention is a latent heat storage microcapsule comprising:

[0016] A core comprising gallium or a gallium alloy, and

[0017] A shell covers the core and comprises gallium hydrate.

[0018] Another embodiment of the present invention is a method for producing a latent heat storage microcapsule, characterized by comprising:

[0019] A particle forming step of forming liquid gallium or gallium alloy into particles;

[0020] A water treatment step of heating the particles in distilled water to form gallium hydrate on the surface of the particles; and

[0021] An oxidation treatment step of oxidizing the gallium hydrate to form a shell composed of gallium oxide.

[0022] Another embodiment of the present invention is a method for producing a latent heat storage microcapsule, characterized by comprising:

[0023] A particle forming step of forming liquid gallium or gallium alloy into particles;

[0024] A cooling step of cooling the particles to form a solid state; and

[0025] A pH treatment step of immersing the particles in an aqueous solution of a predetermined pH to form a shell containing gallium hydrate.

[0026] Effects of the Invention

[0027] The latent heat storage microcapsule of the embodiment of the present invention can provide a thermal storage material having high thermal conductivity and thermal storage density and a flexible shape.

[0028] Furthermore, the method for producing a latent heat storage microcapsule according to the embodiment of the present invention can provide a latent heat storage microcapsule having high thermal conductivity and thermal storage density and high thermal durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram explaining the latent heat storage microcapsule according to the embodiment of the present invention.

[0030] Figure 2 is the relationship between the weight ratio of β-Ga2O3 in the mixture shell and the heat storage capacity based on weight.

[0031] Figure 3 This is a diagram for explaining a method for producing a latent heat storage microcapsule in which liquid gallium is covered with a shell.

[0032] Figure 4 These are SEM photographs of the surface when the oxidation temperature in the oxidation treatment step was changed.

[0033] Figure 5 This is the result of examining the gallium oxide forming the shell using XRD.

[0034] Figure 6 It is the result of differential scanning calorimetry of latent heat / melting point.

[0035] Figure 7 These are SEM photographs of samples after chemical conversion treatment and oxidation treatment before and after repeated heat storage and release tests.

[0036] Figure 8 It is the relationship between the number of phase changes (cycles) and the normalized latent heat and phase change temperature for the samples after oxidation treatment, and the surface SEM photos of the samples after repeated heat storage and release tests.

[0037] Fig. 9 This is a diagram for explaining a method for producing a latent heat storage microcapsule in which liquid gallium is covered with a shell.

[0038] Fig.10 These are SEM photographs of latent heat storage microcapsules after chemical conversion treatment at 80°C and 100°C.

[0039] Fig.11 These are the XRD analysis results of the shell when the water treatment temperature was 80° C. and 100° C. and the water treatment time was 3 hours.

[0040] Fig.12 Is for Fig.11 The results were obtained by measuring the latent heat of the same sample.

[0041] Fig.13 These are SEM photographs of latent heat storage microcapsules after water treatment when the water treatment time was set to 15 minutes, 3 hours, and 5 hours.

[0042] Fig.14This is a SEM photograph of the latent heat storage microcapsule when the water treatment time is 5 hours and the treatment temperature is 100°C.

[0043] Fig.15 These are the XRD analysis results of the shell when the water treatment temperature was set to 100° C. and the water treatment time was changed.

[0044] Fig.16 Is for Fig.15 The results were obtained by measuring the latent heat of the same sample.

[0045] Fig.17 is the result of the thermal durability test of GaOOH shell.

[0046] Fig.18 These are the SEM-EDS results of the cross-section after the water treatment step and the oxidation treatment step.

[0047] Fig.19 This is a diagram for explaining a method for producing a latent heat storage microcapsule in which solid gallium is covered with a shell.

[0048] Fig. 20 These are SEM photographs of the surface of the latent heat storage microcapsule when the pH treatment conditions were changed.

[0049] Fig.21 This is a cross-sectional SEM photograph of a latent heat storage microcapsule treated at pH 11 for 5 hours.

[0050] Fig. 22 is for Fig. 20 The results of X-ray diffraction of 6 samples were obtained.

[0051] Fig.23 It is the relationship between the oxidation treatment time and the weight change during the oxidation treatment.

[0052] Fig.24 is for Fig. 20 The differential scanning calorimetry results of the latent heat of 6 samples.

[0053] Fig.25 These are SEM photographs of samples treated for 5 hours at pH 11 before and after repeated heat storage and release tests.

[0054] Fig.26 This is a SEM photograph of the surface of the latent heat storage microcapsule after stirring in a solution with a pH of 7 to 11 for 5 hours.

[0055] Fig. 27 is for Fig.26 The results of X-ray diffraction of 6 samples were obtained.

[0056] Fig.28is for Fig.26 The differential scanning calorimetry results of the latent heat of 6 samples.

[0057] Fig.29 These are the results of differential scanning calorimetry of melting / solidification of latent heat storage microcapsules and Ga treated in solutions at pH 9 and 11.

[0058] Fig.30 These are surface SEM photographs of latent heat storage microcapsules treated in solutions of pH 9 and 11 before and after repeated tests. DETAILED DESCRIPTION

[0059] 1. Latent heat storage microcapsules

[0060] Figure 1 Schematic diagram of a latent heat storage microcapsule (hereinafter also referred to as "microcapsule") for explaining an embodiment of the present invention. In an embodiment of the present invention, gallium, which is a PCM (Phase Change Material), is used as a latent heat storage body. Gallium has a melting point of about 29.8°C, and stores heat when it melts from a solid to a liquid near the melting point, and releases heat when it solidifies from a liquid to a solid.

[0061] Therefore, by sealing gallium in microcapsules that do not melt in the temperature range used as latent heat storage materials, the latent heat storage materials can be used in a solid form. In addition, by making microcapsules with a diameter of several tens of μm, the heat transfer area becomes larger and the thermal responsiveness is improved.

[0062] The heat storage material is formed by an aggregate of latent heat storage microcapsules with a diameter of tens of μm, so the size and shape can be arbitrarily changed. Therefore, it can be placed inside electric vehicles, etc. where the space for placing heat storage materials is extremely limited.

[0063] like Figure 1 As shown in the right figure, the latent heat storage microcapsule includes: a core containing gallium (Ga) and a shell (capsule) containing gallium oxide or gallium hydrate (Ga2O3 or GaOOH).

[0064] (1) Gallium / Gallium Oxide Microcapsules

[0065] When the core of the latent heat storage microcapsule contains gallium (Ga) and the shell contains gallium oxide, the gallium oxide (Ga2O3) contains β-Ga2O3 or a mixture of β-Ga2O3 and α-Ga2O3.

[0066] Figure 2The relationship between the weight ratio of β-Ga2O3 to the total mixed shell ((β-Ga2O3) / (α-Ga2O3+β-Ga2O3)) and the heat storage capacity based on weight is shown when the volume ratio of the mixed shell in the latent heat storage microcapsule is 0.1. Figure 2 It is known that the higher the ratio of β-Ga2O3, the higher the heat storage capacity of the microcapsule based on weight. As such, it is preferred that the ratio of β-Ga2O3 in the shell is high, for example, the weight ratio is preferably in the range of 0.7 or more and 1 or less.

[0067] For a microcapsule whose shell is completely composed of β-Ga2O3, when the volume ratio of the shell is 0.1, the thermal storage density becomes about 426 MJ / m 3 This is in contrast to the thermal storage density (about 180 MJ / m 3 ) is about 2.4 times the size.

[0068] The microcapsule is roughly spherical, with a diameter of 20 μm or more and 60 μm or less, preferably 30 μm or more and 40 μm or less. In addition, the film thickness of the shell containing gallium oxide is preferably 0.5 μm or more and 1.0 μm or less, for example. The ratio of the radius r1 of the microcapsule to the film thickness r2 of the shell (r2 / r1) is preferably 0.025 or more and 0.07 or less.

[0069] By making the microcapsule into a sphere with a diameter of about 20 μm to 60 μm, the heat transfer area (surface area of ​​the microcapsule) can be increased. In addition, the thermal conductivity of the core is about 40 W / mK. This is about 200 times the thermal conductivity (about 0.21 W / mK) of the core of the microcapsule recorded in Patent Document 1, which is obtained by setting the core as a paraffin-based organic compound.

[0070] In addition, the density of the microcapsule is 5910kg / m 3 This is in contrast to the density of the microcapsules described in Patent Document 1, which have a core made of a paraffin-based organic compound (approximately 900 kg / m 3 ) is more than 6 times the size.

[0071] In the microcapsule of the embodiment of the present invention, when gallium becomes solid below the melting point, the volume of the internal space of the shell is formed to be equal to or larger than the volume of gallium. Therefore, when the microcapsule is used for heat storage, even if the volume of gallium increases due to phase change, the core will not be damaged, and a microcapsule with high reliability can be formed.

[0072] It should be noted that, in addition to pure gallium, the metal of the core may also be a gallium alloy such as Ga-In, Ga-Sn, Ga-Zn, etc. The melting point of the core can be changed by adding In, Sn, Zn, etc.

[0073] In addition, in the microcapsule, a region containing both Ga or a Ga alloy and Ga 2 O 3 may be included at the boundary between the core containing gallium or a gallium alloy and the shell containing a gallium oxide.

[0074] (2) Gallium / Gallium Hydrate Microcapsules

[0075] When the core of the latent heat storage microcapsule contains gallium (Ga) and the shell contains a gallium hydrate, the gallium hydrate contains, for example, GaOOH.

[0076] The microcapsule is roughly spherical, and has a diameter of 20 μm or more and 60 μm or less, preferably 30 μm or more and 40 μm or less. In addition, the film thickness of the shell containing gallium hydrate is preferably, for example, 0.5 μm or more and 1.0 μm or less. The ratio of the radius r1 of the microcapsule to the film thickness r2 of the shell (r2 / r1) is preferably 0.025 or more and 0.07 or less.

[0077] In the microcapsule of the embodiment of the present invention, when gallium becomes solid below the melting point, the volume of the internal space of the shell is formed to be equal to or larger than the volume of gallium. Therefore, when the microcapsule is used for heat storage, even if the volume of gallium increases due to phase change, the core will not be damaged, and a microcapsule with high reliability can be formed.

[0078] It should be noted that, in addition to pure gallium, the metal of the core may also be a gallium alloy such as Ga-In, Ga-Sn, Ga-Zn, etc. The melting point of the core can be changed by adding In, Sn, Zn, etc.

[0079] In addition, in the microcapsule, a region containing both Ga or a Ga alloy and Ga 2 O 3 may be included at the boundary between the core containing gallium or a gallium alloy and the shell containing a gallium oxide.

[0080] 2. Method for manufacturing latent heat storage microcapsules

[0081] When gallium solidifies from liquid to solid, its volume expands by 3.2%. Therefore, in microcapsules obtained by covering liquid gallium with a solid shell, there is a problem that the volume of gallium expands when gallium solidifies, causing the microcapsules to break.

[0082] In an embodiment of the present invention, as described above, the volume of the internal space of the shell is made equal to or larger than the volume of the gallium when the gallium of the core becomes solid below the melting point. In the production of such microcapsules, the following production methods are used: (1) in the case of covering liquid gallium with a shell, the gallium is heated from the melting point and covered with the shell in a state where the volume is expanded by 3.2% or more (the volume is about 1.03 times or more); or (2) the gallium is cooled to below the melting point, made into a solid state, and covered with the shell.

[0083] Hereinafter, the method for manufacturing the latent heat storage microcapsule according to the embodiment of the present invention will be described in the order of (1) a method for manufacturing gallium in a liquid state covered with a shell, and (2) a method for manufacturing gallium in a solid state covered with a shell. It should be noted that the method (1) corresponds to the method for manufacturing gallium / gallium oxide microcapsules, and the method (2) corresponds to the method for manufacturing gallium / gallium hydrate microcapsules.

[0084] (1) Method for producing liquid gallium covered with a shell

[0085] :Method for producing gallium / gallium oxide microcapsules

[0086] (1-1) Manufacturing method

[0087] Figure 3 1 is a diagram for explaining a method for manufacturing a latent heat storage microcapsule of gallium in a liquid state covered with a shell. The manufacturing method includes Figure 3 The three steps [1] to [3] are shown.

[0088] [1] Gallium particle production process

[0089] A thin film rotary mixer was prepared, and 1.0 g of gallium and 10 ml of distilled water were added to the reaction container. The temperature of the distilled water was kept at 40° C., which was higher than the melting point of gallium (about 29.8° C.). The melting point of gallium was about 29.8° C., so gallium was liquid in this state.

[0090] Next, the rotor was rotated at 16,000 rpm for 30 minutes to stir the distilled water to which gallium had been added, thereby dispersing liquid gallium particles having a diameter of about 30 μm in the distilled water.

[0091] [2] Chemical conversion treatment (water treatment) process

[0092] Further distilled water was added to the distilled water in which the liquid gallium particles were dispersed to make a total of 100 ml. The temperature of the distilled water was maintained at 100° C. and stirred for 3 hours using a hot stirrer. Thus, the surface of the gallium particles was covered with a thin layer of gallium hydrate, such as GaOOH.

[0093] [3] Oxidation treatment process

[0094] The gallium particles are taken out of the distilled water and subjected to oxidation treatment. In an oxygen atmosphere, the temperature is maintained at a range of 300°C to 700°C, for example, 600°C for 3 hours. In this process, the GaOOH film is transformed into a solid gallium oxide film by a dehydration reaction. In addition, as the volume of Ga as a core expands, cracks occur in the gallium oxide film, and at the same time, the liquid Ga present near the cracks reacts instantly with the oxygen in the atmosphere to form gallium oxide. The gallium oxide generated by the oxidation of the liquid Ga covers the cracked portion of the gallium oxide film originating from the GaOOH film and integrates them, thereby covering the surface of the gallium particles with solid gallium oxide.

[0095] As mentioned above, the melting point of gallium is about 29.8°C, and the volume expands by 3.2% when solidifying from liquid to solid. Therefore, in the microcapsule obtained by covering the liquid gallium with solid gallium oxide, there is a problem that the volume of gallium expands when the gallium solidifies and the microcapsule is damaged. Therefore, in this oxidation treatment process, the surface is oxidized in a state where the volume of the liquid gallium is expanded by 3.2% in advance, and the gallium is covered with solid gallium oxide.

[0096] Specifically, the volume of liquid gallium expands by about 3.2% by heating to about 280° C. Here, heating to 600° C. forms a gallium oxide shell on the surface of gallium.

[0097] Through the above steps, a latent heat storage microcapsule in which a core composed of liquid gallium (Ga) is covered with a shell composed of solid gallium oxide (Ga2O3) is completed.

[0098] (1-2) Evaluation of Gallium / Gallium Oxide Microcapsules

[0099] The latent heat storage microcapsules produced by the production method according to the embodiment of the present invention are subjected to

[0100] Particle surface / cross-section observation (SEM-EDS)

[0101] Shell identification (XRD)

[0102] Latent heat / melting point determination (DSC)

[0103] Repeated heat storage and release test,

[0104] Thus, the latent heat storage microcapsule was evaluated.

[0105] Particle surface / cross-section observation (SEM-EDS)

[0106] Figure 4 These are SEM-EDS photographs of the surface when the oxidation temperature in the oxidation treatment step [3] was set to 300° C., 400° C., 500° C., 600° C., and 700° C. The other oxidation treatment conditions were the same.

[0107] exist Figure 4 In the SEM photos of , the microcapsules that are spherical are those covered with gallium oxide on the surface. When the oxidation temperature is 300°C, 400°C, and 500°C, cracks appear on the surface of the gallium oxide (for example, the microcapsule in the center of the photo at 300°C), and the gallium inside the microcapsule is exposed. On the other hand, such cracks are not seen at 600°C and 700°C. It is believed that this is because even if cracks appear, the exposed gallium is oxidized again and self-repaired.

[0108] As described above, when 600° C. and 700° C. were used as the oxidation treatment temperature, the core was covered with a shell of gallium oxide while the gallium in the core expanded by 3.2% or more, and encapsulation of gallium was successful.

[0109] Shell identification (XRD)

[0110] Figure 5 The results were obtained by examining the gallium oxide that forms the shell using XRD (X-ray diffraction). The samples were chemically converted and oxidized at 600°C in an oxygen atmosphere for 3 hours. In the chemically converted sample, GaOOH (□) was detected together with Ga (○). On the other hand, in the oxidized sample, β-Ga2O3 (△) was detected instead of GaOOH (□).

[0111] Depend on Figure 5 It is known that after the chemical conversion treatment, microcapsules in which the surface of the Ga core is covered with a shell of GaOOH are formed, while on the other hand, after the oxidation treatment, microcapsules in which the surface of the Ga core is covered with a shell of β-Ga2O3 are formed.

[0112] Latent heat / melting point determination (DSC)

[0113] Figure 6 The results of differential scanning calorimetry (DSC) of latent heat / melting point. The left graph shows heat storage (heating up), and the right graph shows heat release (cooling). The horizontal axis shows temperature, and the vertical axis shows heat flow. Figure 6 In the equation, L is the latent heat and Tm is the melting point. Figure 5 same.

[0114] exist Figure 6 In the left figure, the latent heat is 92 J / g for pure Ga, 47.3 (25 + 22.3) J / g after chemical conversion, and 51 J / g after oxidation. In the right figure, the latent heat is 97 J / g for pure Ga, 46 J / g after chemical conversion, and 46 J / g after oxidation. As shown in this way, after chemical conversion and oxidation, about 50% of the latent heat of pure Ga can be maintained.

[0115] On the other hand, regarding the samples after the chemical conversion treatment and the oxidation treatment, a decrease in the melting point (supercooling) was observed compared to pure Ga.

[0116] Repeated heat storage and release test

[0117] Figure 7 These are SEM-EDS photographs of samples after chemical conversion treatment and oxidation treatment before and after repeated heat storage and release tests. Figure 7 The upper part is after chemical conversion treatment. Figure 7 The lower part is after oxidation treatment, and the SEM photos before and after the heat storage test are shown. Figure 5 Regarding repeated heat storage and release, heat storage and release, that is, phase transition between solid phase and liquid phase, was performed 10 times in the temperature range of -80°C to 50°C.

[0118] Depend on Figure 7 It can be seen that in the sample after chemical conversion treatment (Ga core and GaOOH shell), damage was confirmed in part of the shell after the test. On the other hand, in the sample after oxidation treatment (Ga core and β-Ga2O3 shell), although some particles were observed to aggregate, there was no damage to the shell, which confirmed that it had become a good microcapsule.

[0119] Figure 8 The relationship between the number of phase changes (cycles) and the normalized latent heat and phase change temperature when the phase change between solid and liquid phases (melting and solidification combined 10 times) is repeated 10 times as a repeated heat storage and release test for the sample after oxidation treatment (oxidation temperature: 600°C), and the surface SEM photograph of the sample after the repeated heat storage and release test. The horizontal axis is the number of phase changes (cycles), and the vertical axis is the normalized latent heat and phase change temperature. Normalization is expressed as the value when the initial value is set to 1 (the value obtained by dividing the value of the first phase change).

[0120] Depend on Figure 8 It can be seen that even if the phase transition between the solid phase and the liquid phase is repeated 10 times, the melting latent heat, solidification latent heat, melting temperature, and solidification temperature hardly change, and the changes are within the range of ±0.0001 relative to the initial value. In other words, it can be seen that the heat storage and release characteristics are stable even if the phase transition is repeated.

[0121] In addition, if you watch Figure 8 From the SEM photographs, although leakage and aggregation of Ga nuclei were observed in some samples, the particles basically maintained a spherical shape, which suggests that the heat storage and release characteristics were also stable.

[0122] As described above, by performing [1] the gallium particle preparation step, [2] the chemical conversion treatment (water treatment) step, and [3] the oxidation treatment step, a microcapsule was obtained in which Ga was expanded by 3.2% in volume and covered with a β-Ga2O3 shell. In the microcapsule, about 50% of the latent heat of pure Ga was obtained. In addition, the result of repeated heat storage and release tests showed that there was almost no damage to the shell, indicating that stable heat storage and release characteristics were obtained.

[0123] (1-3) Adjustment of Shell Film Thickness

[0124] For microcapsules obtained by covering Ga cores with β-Ga2O3 shells, the shell film thickness is adjusted by changing the chemical conversion treatment (water treatment) conditions [2]. Fig. 9 The present invention shows a method for producing microcapsules by fixing [1] gallium particle preparation conditions and [3] oxidation treatment conditions and changing [2] chemical conversion treatment (water treatment) conditions. The following evaluation was performed on samples that had undergone [1] gallium particle preparation steps, [2] chemical conversion treatment (water treatment) steps, and before [3] oxidation treatment steps. In other words, the shell was evaluated in the state of a precursor of the β-Ga2O3 shell.

[0125] Except that the temperature of the distilled water was set at 35°C, the gallium particle preparation conditions were the same as those in [1]. Figure 1 In addition, [2] in the chemical conversion treatment (water treatment), the temperature is selected within the range of 60°C to 100°C, and the treatment time is also selected within the range of 5 minutes to 5 hours.

[0126] For the prepared microcapsules,

[0127] Particle surface observation (SEM-EDS)

[0128] Shell identification (XRD)

[0129] Latent heat / melting point determination (DSC)

[0130] Repeated heat storage and release test,

[0131] Evaluation of latent heat storage microcapsules was performed.

[0132] Particle surface observation (SEM-EDS)

[0133] Fig.10The SEM photographs of the microcapsules after chemical conversion treatment (water treatment) at 80°C and 100°C are shown in the following figure, when the water treatment temperature is set to 60°C, 70°C, 80°C, and 100°C and the water treatment time is set to 3 hours. The upper part is a surface photograph and the lower part is a cross-sectional photograph. When the water treatment temperature is set to 80°C and 100°C, it can be seen that a shell (GaOOH crystal) is formed on the surface of the Ga core. Regarding the film thickness of the shell, the film thickness at 100°C is thicker than that at 80°C. On the other hand, in the samples obtained by setting the chemical conversion treatment temperature to 60°C and 70°C, no precipitate is formed on the surface.

[0134] Shell identification (XRD)

[0135] Fig.11 The XRD analysis results of the shell are shown in the case where the water treatment temperature is set to 80°C and 100°C, where the shell is precipitated on the surface of the Ga core, and the water treatment time is set to 3 hours. In the samples treated with water at 80°C and 100°C, peaks caused by GaOOH that are not seen in the Ga particles before water treatment are confirmed, and it can be seen that GaOOH is precipitated as a shell. In particular, a larger peak is seen in the sample treated with water at 100°C. It is believed that the GaOOH becomes β-Ga2O3 in the subsequent oxidation treatment.

[0136] Latent heat / melting point determination (DSC)

[0137] Fig.12 Is for Fig.11 The same sample, the results of the latent heat determination are Fig.12 In the graph, the horizontal axis represents temperature and the vertical axis represents heat flow. For Ga particles, the latent heat is 82 J / g, but for samples at 80°C and 100°C, the latent heat is 56 J / g and 46 J / g, respectively. It is believed that by covering the Ga core with a GaOOH shell, the latent heat becomes smaller. In particular, it is believed that the film thickness of the shell of the 100°C sample is larger than that of the 80°C sample. In addition, a decrease in the melting point (supercooling) was observed in the 80°C and 100°C samples.

[0138] Next, according to Figure 10 to Figure 12 The results were obtained by using a water treatment temperature of 100°C at which the film thickness was the thickest and the chemical conversion treatment time was set to 5 minutes, 15 minutes, 3 hours, and 5 hours.

[0139] Particle surface observation (SEM-EDS)

[0140] Shell identification (XRD)

[0141] Latent heat / melting point determination (DSC)

[0142] Repeated heat storage and release test,

[0143] Evaluation of latent heat storage microcapsules was performed.

[0144] Particle surface observation (SEM-EDS)

[0145] Fig.13 The SEM photos of the water-treated microcapsules are shown in the figure below when the water treatment time is set to 15 minutes, 3 hours, and 5 hours. The upper part is a surface photo and the lower part is a cross-sectional photo. The water treatment temperature is 100°C. It can be seen that a shell (GaOOH crystal) is formed on the surface of the Ga core when the water treatment time is more than 15 minutes. The longer the water treatment time, the thicker the shell film becomes. It should be noted that in the sample with a water treatment time of 5 minutes, no precipitate is formed on the surface.

[0146] Fig.14 The water treatment time is 5 hours and the treatment temperature is 100℃( Fig.13 The shape is slightly deformed from the spherical shape, but it can be seen that a thick shell is formed.

[0147] Shell identification (XRD)

[0148] Fig.15 The XRD analysis results of the shells are shown when the water treatment temperature is set to 100°C and the water treatment time is set to 15 minutes, 1 hour, 3 hours, and 5 hours. In the samples obtained by water treatment for more than 15 minutes, peaks due to GaOOH that are not seen in the Ga particles before water treatment are confirmed, indicating that GaOOH is precipitated as a shell.

[0149] Latent heat / melting point determination (DSC)

[0150] Fig.16 Is for Fig.15 The same sample, the results of the latent heat determination are Fig.16 In the graph, the horizontal axis represents temperature and the vertical axis represents heat flow. The water treatment temperature is 100°C. For Ga particles, the latent heat is 82 J / g, but for samples with water treatment time of 15 minutes, 1 hour, 3 hours, and 5 hours, the latent heat is 57 J / g, 36 J / g, and 54 J / g, respectively. It is believed that by covering the Ga core with a GaOOH shell, the latent heat becomes smaller. In addition, a decrease in the melting point (supercooling) was observed in each sample.

[0151] As described above, it is known that under the specified water treatment conditions, a GaOOH shell is formed on the surface of the Ga particles. In particular, the higher the water treatment temperature and the longer the water treatment time, the thicker the shell film becomes. The GaOOH shell is considered to be the so-called precursor of the β-Ga2O3 shell formed via the oxidation step [3].

[0152] (1-4) Thermal durability test of GaOOH shell

[0153] Fig.17 The results of the thermal durability test of the GaOOH shell formed on the surface of Ga particles show that Fig.17 In the figure, the horizontal axis represents the heating time, and the vertical axis represents the weight change rate and the heating temperature. Fig.17 In FIG. 1 , a temperature curve (dashed line) and a TG curve (solid line) are shown.

[0154] When the temperature is increased at a certain rate, when the temperature of the sample exceeds about 250°C, the mass of the sample decreases as shown in the TG curve. This is believed to be due to the dehydration of the GaOOH shell, resulting in the following reaction:

[0155] 2GaOOH→Ga2O3+H2O

[0156] (1-5) SEM and EDS after water treatment and oxidation treatment

[0157] Fig.18 It is used Fig. 9 The method shown is the result of SEM (scanning electron microscope) observation and EDS (X-ray diffraction analysis) of the cross section of the sample after [2] the water treatment step and [3] the oxidation treatment step, respectively.

[0158] [2] The water treatment conditions were a treatment temperature of 100° C. and a treatment time of 3 hours, which formed a good GaOOH shell. [3] The oxidation treatment conditions were an oxygen atmosphere, a treatment temperature of 600° C. and a treatment time of 3 hours.

[0159] exist Fig.18 In the figure, the upper part is after the [2] chemical conversion treatment (water treatment) step, and the lower part is after the [3] oxidation treatment step. In addition, the two pictures on the left are SEM pictures of the cross section, and the other four pictures are EDS results of Ga and O. From the SEM pictures, it can be seen that a shell is formed on the surface in both the [2] water treatment step and the [3] oxidation treatment step. In addition, from the results of EDS, it can be seen that a compound of Ga and O is formed on the surface. The [3] oxidation treatment step is carried out at 600°C, which is higher than the decomposition temperature of GaOOH of 250°C. Therefore, it is believed that the shell after the [2] water treatment step is GaOOH, and the shell after the [3] oxidation treatment step is β-Ga2O3.

[0160] The shell film thickness is approximately the same after the water treatment step [2] and after the oxidation treatment step [3], which is 1 to 2 μm. This shows that by adjusting the treatment conditions (temperature, time) of the water treatment step [2] and controlling the film thickness of the GaOOH shell, the film thickness of the Ga2O3 shell after the oxidation treatment step [3] can also be controlled.

[0161] (2) Method for producing solid gallium covered with a shell

[0162] :Method for producing gallium / gallium hydrate microcapsules

[0163] (2-1) Manufacturing method

[0164] Fig.19 1 is a diagram for explaining a method for manufacturing a latent heat storage microcapsule of solid gallium covered with a shell. The manufacturing method includes Fig.19 The three steps [1] to [3] are shown.

[0165] [1] Gallium particle production process

[0166] A thin film rotary mixer was prepared, and 1.0 g of gallium and 10 ml of distilled water were added to the reaction container. The temperature of the distilled water was maintained at 35° C. The melting point of gallium is about 29.8° C., so gallium is liquid in this state.

[0167] Next, the rotor was rotated at a rotation speed of 16000 rpm for 10 minutes to stir the distilled water to which gallium had been added, thereby dispersing liquid gallium particles having a diameter of about 30 μm in the distilled water.

[0168] [2] Gallium particle cooling process

[0169] The liquid gallium particles are taken out, placed in a container such as a beaker, and cooled with liquid nitrogen (boiling point: -196°C) for 20 minutes. The gallium particles are thereby solidified to obtain solid gallium particles.

[0170] [3] pH treatment process

[0171] Solid Ga particles are sieved by size, and Ga particles with a diameter of 20μm to 53μm are sorted. Ga particles are placed in distilled water at room temperature (25°C) and stirred with a hot stirrer. Ammonia (1.0 mol / L) is used as a pH adjuster to adjust the distilled water to pH 11. The pH treatment time (immersion time) is selected between 15 minutes and 12 hours, for example, set to 3 hours. As a result, the surface of the solid gallium particles is covered with solid gallium hydrate.

[0172] As described above, the melting point of gallium is about 29.8° C., and the volume expands by 3.2% when solidifying from liquid to solid. Therefore, by covering the solid Ga particles with a solid shell, it is possible to prevent the shell from being damaged by the volume expansion when Ga solidifies.

[0173] Through the above steps, a latent heat storage microcapsule is completed in which a core composed of solid gallium (Ga) is covered with a shell composed of solid gallium hydrate (GaOOH). Fig.17), GaOOH dehydrates to become Ga2O3 above 250℃, so the heat-resistant temperature of gallium / gallium hydrate microcapsules is lower than 250℃, and the use environment is also limited to below about 250℃.

[0174] (2-2) Adjustment of processing time

[0175] In the [3] pH treatment step, the treatment time was adjusted. The pH of the solution to which Ga was added was fixed at 11, the temperature of the solution was fixed at room temperature (25°C), and the treatment time for stirring with a hot stirrer was set to 15 minutes, 1 hour, 3 hours, 5 hours, 8 hours, and 12 hours.

[0176] Particle surface / cross-section observation (SEM-EDS)

[0177] Shell identification (XRD)

[0178] Latent heat determination (DSC)

[0179] Repeated heat storage and release test,

[0180] Evaluation of latent heat storage microcapsules was performed.

[0181] Particle surface observation (SEM-EDS)

[0182] Fig. 20 The SEM photographs of the surface of the latent heat storage microcapsule after stirring in a solution of pH 11 for 15 minutes, 1 hour, 3 hours, 5 hours, 8 hours, and 12 hours. If the treatment time is 3 hours or more, a honeycomb structure is seen on the surface of the microcapsule. It is believed that Ga hydrate GaOOH is formed around the Ga particles.

[0183] Fig.21 This is a SEM photograph of a cross section of a microcapsule when the pH is 11 and the treatment time is 5 hours. A shell with a film thickness of about 0.5 μm was confirmed around the Ga particles. As described above, it is believed that the shell is composed of GaOOH.

[0184] Shell identification (XRD)

[0185] Fig. 22 It is to identify the substances on the surface of microcapsules. Fig. 20 The results of X-ray diffraction (XRD) of 6 samples were obtained. No peaks other than Ga were confirmed in any of the samples. Fig. 20 The honeycomb structure of GaOOH was considered to be in an amorphous state rather than a crystalline state, so it was considered that GaOOH was not detected in XRD.

[0186] Next, in order to examine whether the honeycomb structure formed on the surface of the microcapsule is GaOOH, the sample obtained after the pH treatment step [3] (pH 11 × 5 hours) was subjected to oxidation treatment to examine the weight change. The oxidation treatment was performed in an oxygen atmosphere (O2 flow rate: 200 ml / min) for more than 30 minutes.

[0187] Fig.23 The relationship between the oxidation treatment time and the weight change during the oxidation treatment is shown in Figure 1. The horizontal axis is the oxidation treatment time, and the vertical axis is the weight change rate and the treatment temperature. Fig. 22 It can be seen that the weight starts to decrease immediately after heating, and after 20 minutes, the weight becomes substantially constant.

[0188] This weight reduction is considered to be based on

[0189] 2GaOOH→Ga2O3+H2O

[0190] The dehydration of GaOOH is believed to be Fig. 20 The honeycomb structure is GaOOH.

[0191] Latent heat determination (DSC)

[0192] Fig.24 is for Fig. 20 The results of differential scanning calorimetry (DSC) of the latent heat of 6 samples. The measurement was performed by cooling from 50°C to -80°C at a cooling rate of 2°C / min. The atmosphere was set to Ar atmosphere, and the Ar flow rate was set to 50ml / min. The latent heat of the Ga particles before treatment was 82J / g. In contrast, the latent heat was also 85J / g when the treatment time was 12 hours, and no significant difference was seen in the latent heat between the samples. It is believed that this is because even if the treatment time is extended, the amount of GaOOH precipitated around the Ga particles, that is, the film thickness of the GaOOH shell, does not change much.

[0193] Repeated heat storage and release test

[0194] Fig.25 The SEM photographs before and after the repeated heat storage and release test of the sample at pH 11 and the treatment time of 5 hours are shown. The left is the SEM photograph before the durability test, and the right is the SEM photograph after the durability test. Regarding the repeated heat storage and release, 10 times of heat storage and release, that is, the phase transition between the solid phase and the liquid phase, were performed in the temperature range of -80°C to 50°C. The atmosphere was Ar atmosphere, and the Ar flow rate was set to 50 ml / min.

[0195] From the SEM photograph after the durability test, it can be seen that although holes and leakage were observed in a part of the shell, the microcapsule formed under this condition showed good durability in repeated tests.

[0196] As described above, in the pH treatment step [3], the treatment time is set to at least 5 hours under the condition of pH 11, thereby obtaining a latent heat storage microcapsule having a GaOOH shell formed so as to cover the Ga particles. In the microcapsule, the latent heat amount that does not change from that of the Ga particles is obtained, good heat storage and release characteristics are obtained, and good repeated durability is obtained.

[0197] (2-3) pH adjustment

[0198] In the [3] pH treatment step, the pH is adjusted. The pH of the solution to which Ga is added is set to 7, 8, 9, 10, or 11. The temperature of the solution is fixed to room temperature (25°C), and the treatment time for stirring with a hot stirrer is set to 5 hours.

[0199] Particle surface observation (SEM-EDS)

[0200] Shell identification (XRD)

[0201] Latent heat determination (DSC),

[0202] Evaluation of latent heat storage microcapsules was performed.

[0203] Particle surface observation (SEM-EDS)

[0204] Fig.26 The SEM photographs of the surface of the latent heat storage microcapsule after stirring for 5 hours at room temperature (25°C) in a solution with pH values ​​of 7, 8, 9, 10, and 11. When the treatment time is 3 hours or more, a honeycomb structure is observed on the surface of the microcapsule. It is believed that Ga hydrate GaOOH is formed around the Ga particles.

[0205] Shell identification (XRD)

[0206] Fig. 27 Yes Fig.26 The results of X-ray diffraction (XRD) of 6 samples were obtained. In the samples with pH 8, 9, and 10, GaOOH peaks were observed.

[0207] Ga 2+ +2OH - →GaOOH+1 / 2H2

[0208] As a result, GaOOH, a hydrate of Ga, is formed around Ga. On the other hand, no peak of GaOOH is observed in the sample at pH 11. This is considered to be because, as described in "(2-2) Adjustment of treatment time", under the condition of pH 11, GaOOH becomes an amorphous state. Fig. 27 Among them, the peak of GaOOH is the largest at pH 9.

[0209] Latent heat determination (DSC)

[0210] Fig.28 is for Fig.26 The results of differential scanning calorimetry (DSC) of the latent heat of 6 samples. The measurement was performed by cooling from 50°C to -80°C at a cooling rate of 2°C / min. The atmosphere was set to Ar atmosphere, and the Ar flow rate was set to 50ml / min. The latent heat of Ga particles before treatment was 82J / g. In contrast, under the conditions of pH 7, 8, 9, 10, and 11, the latent heat was 97J / g, 73J / g, 61J / g, 81J / g, and 74J / g, respectively.

[0211] The latent heat becomes smaller under the condition of pH 9, which is considered to be because the film thickness of GaOOH as the shell is the largest.

[0212] Fig.29 The results of differential scanning calorimetry of the melting / solidification of latent heat storage microcapsules and Ga obtained by treatment in solutions at pH 9 and 11. The horizontal axis is temperature, and the vertical axis is heat flow, showing the results of the measurement of MEPCM-9 (pH 9), MEPCM-11 (pH 11), and Ga particles. Regarding the latent heat during solidification, it is 85 J / g for pure Ga, while it is 61 J / g for MEPCM-9 and 86 J / g for MEPCM-11. In addition, regarding the latent heat during melting, it is 83 J / g for pure Ga, while it is 59 J / g for MEPCM-9 and 88 J / g for MEPCM-11. As can be seen from this, by treating in a solution at pH 11, a latent heat closer to that of pure Ga is obtained compared to the case of treating in a solution at pH 9.

[0213] Fig.30 The following are surface SEM photographs of samples before and after repeated heat storage and release tests (number of repetitions: 10 times) were performed on MEPCM-9 (pH9) and MEPCM-11 (pH11). Regarding MEPCM-9 (pH9), protrusions caused by the leakage of Ga nuclei were observed on the surface of the sample after the repeated heat storage and release test. On the other hand, regarding MEPCM-11 (pH11), the spherical shape of the sample was maintained before and after the repeated heat storage and release test, and no protrusions were observed. As shown in this way, by optimizing the pH of the aqueous solution in the water treatment process (pH11), the shape of the sample can be maintained even if repeated heat storage and release is performed, and good heat storage and release characteristics are obtained.

[0214] As described above, by adjusting the pH and treatment time of the pH treatment step [3], a good GaOOH shell can be formed around the solid gallium core, thereby obtaining good heat storage and release characteristics. GaOOH may also be in a honeycomb-like amorphous state.

[0215] Industrial Applicability

[0216] The latent heat storage microcapsule of the present invention can be used as a flexible heat storage material in electric vehicles and the like.

Claims

1. A method for producing a latent heat storage microcapsule, characterized in that include: The process of converting liquid gallium into particles. a water treatment step of heating the particles in distilled water to form gallium hydrate on the surface of the particles, and an oxidation treatment step of oxidizing the gallium hydrate to form a shell composed of β-Ga2O3, The oxidation treatment step is performed at a temperature of 600° C. or higher and 700° C. or lower. The temperature of the water treatment process is 80°C to 100°C.

2. A latent heat storage microcapsule, characterized in that: Obtained by the method for producing latent heat storage microcapsules according to claim 1, The latent heat storage microcapsule is composed of a two-layer structure of a core and a shell covering the core. The core is composed of gallium, The shell is composed of β-Ga2O3, The volume of the interior of the shell is 1.03 times or more the volume of the core in a liquid state at a melting point temperature.

3. The latent heat storage microcapsule according to claim 2, characterized in that: The particle size of the latent heat storage body microcapsule is 20 μm or more and 60 μm or less.

4. The latent heat storage microcapsule according to claim 2 or 3, characterized in that: The ratio of the radius r1 of the latent heat storage microcapsule to the film thickness r2 of the shell, that is, r2 / r1, is 0.025 or more and 0.07 or less.

Citation Information

Patent Citations

  • Vehicular control apparatus

    JP2016215745A

  • Core-shell high temperature heat storage material and method of manufacturing the same

    KR1020190036278A

  • Self-strengthening polymer composites

    US20180257322A1